Effect of Compensation on Productivity and the Mediating Role of Competence on the Effect of Employee Training on Productivity - Miswanto, Miswanto; Hermawan, Wisnu Adi (International Journal of Psychosocial Rehabilitation, 2020)
Human resources are the most important assets in an organization. Therefore, the factors that influence its productivity need to be examined. This research aims to examine: 1) the effect of compensation and employee training on productivity, and 2) the mediating role of competence on the effect of employee training on productivity. This research is a case study at the General Directorate of Oil and Gas, Ministry of Energy and Mineral Resources, Republic of Indonesia. The sample of employees is 150 people. The data used are primary data obtained by giving questionnaires to respondents. Designing an instrument to measure variables uses Likert scale. The research findings show that 1) compensation and employee training have a positive effect on productivity, 2) employee training has a positive effect on competence, and 3) competence has a positive effect on productivity. Therefore, competence partially mediates the effect of employee training on productivity